Bridging nir fluorescence molecular guidance to clinical translation in surveillance colonoscopy - Garcia-Allende, P. Beatriz; Glatz, Jürgen; Tjalma, Jolien; Terwissch, Anton; Scheltinga, van; Koorstra, Jan Jacob; Kleibeuker, Jan H.; Dam, Go van; Nagengast, Wouter B.; Ntziachristos, Vasilis (Optical Molecular Probes, Imaging and Drug Delivery, OMP 2013, 2013)
Fluorescence molecular endoscopy is expected to have outstanding relevance regarding early cancer detection. Two alternative flexible endoscopic fluorescence imaging methods that facilitate clinical use of this potential are proposed and characterized in an animal study. ©2013 The Optical Society (OSA).
CRIS-Team Scopus Importer:2023-03-08